Detection of the presence Aeromonas sp on nile tilapia cultured in floating net cage in lake Tondano - Tantu, Wandalia; Tumbol, Reiny A; Longdong, Sammy N.J (Universitas Sam Ratulangi, 2013)
The purpose of this study was to detect the presence of bacteria Aeromonas sp in tilapia (Oreochromis niloticus). Nine fish with an average body weight of 150-200 g were used in this study as samples. Sampling was conducted at three different locations which were representative of fish culture sites located on Lake Tondano. The number of sample gathered from each location was and 3 fish which were taken randomly. Fish samples were taken by using a scoop, then the samples were taken alive by placing in an oxygen-filled plastic separately and taken direcly to lab Fish Disease Control and Environmental Center, Tateli, Department of Marine and Fisheries of North Sulawesi province, for examination the presence of bacteria. Isolation of bacteria were conducted by taking samples from gill and kidney. This study was carried out from April - July 2013. Identification of the presence of bacteria was done through a series of observations of colony morphology and gram staining of bacteria, followed by a series of biochemical tests: oxidase test , catalase test , test TSIA , H2S production test , indole test , motility test , citrate test, and test O/F. It could be concluded that 22.22 % of farmed nile tilapia in Lake Tondano were infected with the Aeromonas sp with the following percentage from each site: Paleloan village 7.40% , 7.40% Toulimembet village, and 7.40% Eris village. Keywords: Aeromonas sp, isolation, nile tilapia, floating net cage, Lake Tondano